Translocation and redistribution of sulphur in corn and soybean plants - Silva, Davi José; Venegas, Víctor Hugo Alvarez; Ruiz, Hugo Alberto; Sant'Anna, Renato (Pesquisa Agropecuaria Brasileira, 2003)
The objective of this work was to study the S translocation and redistribution by acropetal and basipetal transport in corn and soybean plants. Plants of both species were cultivated in nutritive solution containing labeled 35S, in a greenhouse. The 35S applied to only one root was absorbed quickly and transported to the shoot, as well as to the other roots cultivated in non-labeled solution. The 35S applied to only one leaf was transported both to acropetal and basipetal direction. However, corn and soybean showed different behaviors in S absorption and redistribution. In spite of having larger root absorption, corn retained great part of that S in the root, while soybean absorbed considerably less, but presented greater translocation efficiency. The upper leaves, mainly the youngest, showed to be the main physiologic sinks for S in soybean plants.